Cases of Pediatric Pyelonephritis: A Single-Center Retrospective Study from an Extended-Spectrum β-Lactamase-Producing Escherichia coli Endemic Area in Japan - Tsujimoto, Misa; Yokoyama, Hiroki; Shimizu, Keita; Yoneda, Naohiro; Sano, Hitoshi; Ueyama, Junichi; Namba, Noriyuki; Tsuji, Yasuhiro (Yonago acta medica, 2023)
Extended-spectrum β-lactamase (ESBL)-producing has been increasingly recognized as the cause of upper urinary tract infection (UTI) in children. We have been using flomoxef at our department since 2017 as the first-line empiric therapy for children diagnosed with UTIs, and we avoid using carbapenems, which are considered the first-line treatment for ESBL-producing . However, reports on the use of flomoxef for UTIs are limited, especially for pediatric patients. The presence of vesicoureteral reflux at the onset of pyelonephritis is a concern. Severe vesicoureteral reflux can lead to repeated UTI and future deterioration of renal function, but the indication for voiding urethrography, which closely examines the presence of vesicoureteral reflux complications, is controversial. We retrospectively reviewed the laboratory findings, treatment, and clinical course of 96 pyelonephritis cases experienced at our department over a 7-year period from April 2014 to March 2021. ESBL-producing were identified as the cause of pyelonephritis in 51% of cases, and this value was significantly higher (88%) in 2017. No significant differences were found in the febrile period or recurrence rate between the flomoxef-initiated group and other antibiotics groups. We also examined clinical indicators to predict vesicoureteral reflux and found no significant differences in ultrasonographic findings of hydronephrosis. In the present series, 51% of all pyelonephritis cases were found to be caused by ESBL-producing , with a significant increase in recent years. Flomoxef may be a useful alternative to carbapenem for ESBL-producing and the initial antibiotic of choice for upper UTIs in children. The indication for voiding cystourethrography should be carefully determined.